The experience of test exercises using in the current control of the knowledge in general stratigraphy in MGRI-RGGU - V. N. Komarov; A. O. Andrukhovich; A. V. Panova (Известия высших учебных заведений: Геология и разведка, 2016)
The capabilities of the different forms of tests using for the current control of the objective assessment of the student’s knowledge in general stratigraphy are analyzed. The brief data on the pedagogic control and tests matter is given. The meaning of the control cards for statistical processing and analysis of the tests results is considered. The efficiency of the test control system for the organization of the self-control for the learning and fixation of the achieved knowledge as well as the realization of the control of self-educational activity of the students. The most difficult material is concluded to be the material, concerning principals of stratigraphy (15,4% of the correct answers) and it’s methods (21,2%). The best knowledge is shown in the branch of different aspects of the stratigraphy’s history (29% of the correct answers). The maximum troubles are established to be erased by the tasks for the correspondence, concerning the classification of the stratones. Within the concrete methods of the dissection and correlation the most difficulties are connected with isotopic investigations and cyclic stratigraphy. The consequent progress in the material studying, concerning the stratigraphic methods, is revealed. The gradual regress of the results in the tasks for the repetition of the material is found which can be connected with the significant increase of the factual material for the remembering.